Teachers in Cinema. A Half-open Perspective of Schools, Knowledge and Education - Areiza Pérez, Érica Elexandra; Universidad de Antioquia (Editorial Pontificia Universidad Javeriana, 2012)
This paper approaches pedagogy adressing three cinematographical productions: Like Stars on Earth, Red Like the Sky and Mona Lisa Smile, focusing on the teacher characters and how they welcome or hinder the life plans of their students. Also, some tensions of education scenes and the role of knowledge in education processes are explored.Transference to practiceThe approach of this paper includes tensions, challenges and contradictions found in schools and teaching practices and relevant for confrontations of teachers with their educational work, with words taken to the classroom, with strategies for the creation of platforms for the development of human beings, their differences and their place on earth. Also, the paper makes a contribution to the field as it discusses the role of knowledge in education processes, stressing the humanizing aspects, as opposed to encyclopedic knowledge, that relate experience and sensitivity while at the same time allowing subjective transformations and generating other ways of constructing knowledge.